Severe role impairment associated with mental disorders: Results of the WHO World Mental Health Surveys International College Student Project - Alonso, J.; Mortier, P.; Auerbach, R.; Bruffaerts, R.; Vilagut, G.; Cuijpers, P.; Demyttenaere, K.; Ebert, D.; Ennis, E.; Gutiérrez-García, R.; Green, J.; Hasking, Penelope; et al. (Wiley-Liss, Inc, 2018)
© 2018 Wiley Periodicals, Inc., a Wiley company. Background: College entrance is a stressful period with a high prevalence of mental disorders. Aims: To assess the role impairment associated with 12-month mental disorders among incoming first-year college students within a large cross-national sample. Methods: Web-based self-report surveys assessing the prevalence of DSM-IV mental disorders and health-related role impairment (Sheehan Disability Scale) were obtained and analyzed from 13,984 incoming first-year college students (Response = 45.5%), across 19 universities in eight countries. Impairment was assessed in the following domains: home management, work (e.g., college-related problems), close personal relationships, and social life. Results: Mean age of the sample was 19.3 (SD = 0.59) and 54.4% were female. Findings showed that 20.4% of students reported any severe role impairment (10% of those without a mental disorder vs. 42.9% of those with at least one disorder, P < 0.01). In bivariate analyses, panic disorder, and mania were associated most frequently with severe impairment (60.6% and 57.5%, respectively). Students reporting three or more mental disorders had almost fivefold more frequently severe impairment relative to those without mental disorders. Multiple logistic regression showed that major depression (OR = 4.0; 95%CI = 3.3, 4.8), generalized anxiety (OR = 3.9; 95%CI = 3.1, 4.8), and panic disorder (OR = 2.9; 95%CI 2.4, 4.2) were associated with the highest odds of severe impairment. Only minimal deviations from these overall associations were found across countries. Conclusion: Mental disorders among first-year college students are associated with substantial role impairment. Providing preventative interventions targeting mental disorders and associated impairments is a critical need for institutions to address.